ANALYSIS OF POLLUTION OF GROUND WATERS IN THE AIRPORT ZONE - Franchuk, G.M.; Antonov, A.M.; Madzhd, S.M.; Zagoruy, Ya.V. (Proceedings of National Aviation University (archive), 2005)
Negative aspect of airport’s activity, which is its harmful influence on the environment, is described, with the emphasis on the ground waters pollution. The pollution of ground waters of the Nyvka river in the zone of international airport Kyiv is analyzed. The levels of waste emission into the river are determined.